The Use of Bikago Beautified Style in Usage Instructions of Food, Beverage, and Pharmaceutical Products - Mulyadi Mulyadi; Suhandano Suhandano; Munandar Aris (IZUMI, 2022)
The current article discusses a linguistic phenomenon, particularly, the use of bikago beautified style, which has been classified as being separate from teineigo since 2007. The discussion covers the forms of this particular linguistic style and the background of its emergence. This research was conducted because, to date, Japanese language studies pertaining to this specific style mostly consisted of researches that are based on spoken data analysis. This is a descriptive-qualitative study. Data were collected from instruction labels of food, beverage, and pharmaceutical products in Japanese provided on the packages of relevant products. Data were gathered based on the content of bikago style element found within a speech. Speeches that do not contain any bikago style element were not included as research data. Research results shows that the number of bikago terms being used on relevant products is very scarce, only consisting of a few words, yet they are distributed in various elements of usage instruction discourse. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor